Manipulative basic Movement Learning Model in Class 6 Primary School Students - Sifra Oppin Paulima sifra; Fahmy Fachrezzy; Hernawan Hernawan; Oman Uju Subandi; Muhamad Syamsul Taufik (UNIB Press, 2024)
The aim of the research is to produce a basic manipulative movement learning model for grade 6 elementary school students. This research was carried out using a Research and Development (R&D) approach. Researchers conducted research referring to the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation). The research sampling technique used in this research was 1 research subject for 30 students. Data analysis used analysis of the effectiveness test of the basic manipulative movement learning model for 6th grade elementary school students using SPSS. The research results are in the form of basic manipulative movement learning models for 6th grade elementary school students. Which presents 25 basic manipulative movement learning models for 6th grade elementary school students. (3) Product Evaluation: That the improvement in the ability of the basic manipulative movement learning model for grade 6 elementary school students was developed based on the results of effectiveness tests using SPSS. The mean difference test obtained with SPSS was obtained mean = -2.235 showing the difference between the pre-test and post-test, the t-count = -7.201, df = 33 and p-value = 0.000 < 0.05 which means there is a difference significant difference between before and after being given the learning treatment model, which means there is a significant difference between before and after being given that there is an increase in the ability of the basic manipulative movement learning model in 6th grade elementary school students.